2010
DOI: 10.1088/0264-9381/27/16/165004
|View full text |Cite
|
Sign up to set email alerts
|

Quasilocal formalism and thermodynamics of asymptotically flat black objects

Abstract: We study the properties of five-dimensional black objects by using the renormalized boundary stress tensor for locally asymptotically flat spacetimes. This provides a more refined form of the quasilocal formalism, which is useful for a holographic interpretation of asymptotically flat gravity. We apply this technique to examine the thermodynamic properties of black holes, black rings and black strings. The advantage of using this method is that we can go beyond the 'thin ring' approximation and compute the bou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 93 publications
(238 reference statements)
1
36
0
Order By: Relevance
“…For this kind of solutions, a cosmological scenario has been provided in [52], where φ ∞ does vary and so the scalar charge appears in the first law of thermodynamics. The problem with this modified first law of thermodynamics is that the dilaton charge, not being protected by a gauge symmetry, is not a conserved charge [53,54]. This charge is non-localized, exists entirely outside the horizon and usually corresponds to a secondary hair [52,53].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this kind of solutions, a cosmological scenario has been provided in [52], where φ ∞ does vary and so the scalar charge appears in the first law of thermodynamics. The problem with this modified first law of thermodynamics is that the dilaton charge, not being protected by a gauge symmetry, is not a conserved charge [53,54]. This charge is non-localized, exists entirely outside the horizon and usually corresponds to a secondary hair [52,53].…”
mentioning
confidence: 99%
“…The problem with this modified first law of thermodynamics is that the dilaton charge, not being protected by a gauge symmetry, is not a conserved charge [53,54]. This charge is non-localized, exists entirely outside the horizon and usually corresponds to a secondary hair [52,53]. Also, in the AdS spacetimes, scalar charges are not compatible with AdS/CFT since no such charge exist in dual CFT.…”
mentioning
confidence: 99%
“…Recently, the Myers-Perry black hole [26] has been of the particular interest due to its rich thermodynamics [27][28][29][30][31][32][33]. This black hole is a direct generalization of the Kerr black hole in higher dimensions with rotation in more than one plane.…”
Section: Jhep04(2015)115mentioning
confidence: 99%
“…Subsequently, Hawking has shown that the black hole has thermal radiation through a quantum field theoretical analysis [2] and studied the thermodynamic phase transition [3]. In particular, the thermodynamics of black holes has been also studied in a cavity to get well-defined canonical ensembles [4][5][6][7][8][9][10][11][12]. In the quasilocal thermodynamics of a black hole, the thermodynamical quantities such as the energy, the temperature, and so on, are related to the size of cavity, whereas the entropy is not since the entropy can be regarded as a conserved Noether charge [13].…”
Section: Introductionmentioning
confidence: 99%